The Impact of Productive Age and Labor Absorption on Economic Growth in Maluku Province - Metekohy, Stellamaris; Sahrul, Sahrul (Jurnal Ekonomi, 2024)
Economic growth is an important indicator in evaluating the success of a country's economic development. Maluku Province shows economic growth conditions that tend to fluctuate or economic instability and significant changes in recent years. The purpose of this study was to determine the effect of productive age and employment on economic growth in Maluku Province in 2014-2023. This research uses a quantitative approach with secondary data obtained from the Central Bureau of Statistics of Maluku Province. The data analysis method uses multiple linear regression analysis with the help of Eviews 12 software. The results show that partially productive age (X1) with a coefficient value of -1.940227 and Prob. of 0.6328 > 0.05%. This means that it has a negative and insignificant effect on economic growth in Maluku Province, while labor absorption (X2) with a coefficient value of 3.280850 and Prob. of 0.3135 > 0.05%, which means it has a positive and insignificant effect on economic growth in Maluku Province. Simultaneously productive age and employment with a Prob. value of 0.000806 < 0.05, meaning that together they have a significant effect on economic growth in Maluku Province in 2014-2023.